Preliminary Experimental Work on Concrete-Fly Ash Compressive Strength Blended with Seawater as Mixing Water - Zulkifli, Firdaus; Md Noor, Nurazuwa (International Journal of Integrated Engineering, 2023)
Fly ash is widely used in the construction sector, but application with seawater has not fully utilised. Seawater is utilised in construction to minimise the scarcity of drinking water. The concrete was strengthened by the utilisation of fly ash. Seawater replacing 100 percent tapwater as mixing water.  Meanwhile, fly ash was substituted with ordinary Portland cement at 10, 20, 30, and 40 percent. To achive the objective, the 100 mm x 100 mm x 100 mm cube size with 0.33 water-cementitious ratio were prepared. All series of mixture were casted  and cured in water for 7 and 28 days. The fly ash blended with seawater in concrete were investigate through its compressive strength. In addition, scanning electron miscroscope were carried out to capture surface image of the specimen. The experimental work result shows, with the existence of fly ash in concrete mixture, it decrease workability, density and compressive strength. Though the decreasing pattern was seen in every series, the structural strength was still deemed adequate.